Kemitraan dalam Pengembangan Potensi Pariwisata (Studi pada Dinas Kebudayaan dan Pariwisata Kabupaten Tulungagung) - Nurhalimah, Zulfaisya (Jurnal Ilmiah Administrasi Publik, 2020)
In order to increase local original revenue (PAD), the potential of the tourism sector is the main attraction in the current era, where the development of the tourism sector is something that must be considered in a logical and realistic way. Tourism is a sector that must continue to be developed by both the central government and regional governments. Because, the tourism sector has an important role in terms of development and income to increase PAD (Local Original Revenue). In the process of developing tourism potential, local governments often encounter several obstacles, namely one of them is the budget problem in the development of tourism which is still relatively small in number, while the tourism potential is large.